Distribution of volumes of plasma channels components between metal granules in working liquids - Shydlovska, N. A.; Zakharchenko, S. M.; Zakharchenko, M. F.; Kulida, M. A.; Zakusilo, S. A.; Yakovenko, R. A. (Національний технічний університет "Харківський політехнічний інститут", 2025)
Expanding the capabilities of a number of modern technologies and improving quality of their products require detailed spark and plasma erosion processes control in metal granules layers (MGL). Problem. Traditional measurement of exclusively electrical parameters of these processes, even in the case of multi-electrode systems, provides only a general vision, not allowing monitoring processes in individual plasma channels. Optical control methods make it possible to simultaneously have information about almost every plasma channel in the MGL. The aim of the article is to study the characteristic components of plasma channels arising as a result of the flow of discharge currents in the MGL and to establish the laws of distribution of their volumes and their ratios. Methodology. During the experiments, photographs of plasma channels resulting from the flow of discharge current pulses between Al granules immersed in distilled water were obtained. Using the specialized ToupView program, the volumes of equivalent ellipsoids of rotation, approximating the colored halos and white cores of the plasma channels were determined. Discrete distributions of the volumes of the halo and cores of plasma channels, as well as their ratios were constructed both with and without procedures for screening out «anomalous» results. The efficiency of approximation of discrete distributions obtained in practice by continuous theoretical distributions Weibull, Rosin-Rammler and log-normal was estimated. Results. It is shown that of all the considered theoretical distributions of halo and cores of plasma channels volumes, as well as their ratios, the most adequate is the log-normal one. Originality. For the first time distributions of volumes of halo and cores of plasma channels were studied and their comparative analysis with the size distributions of erosion particles and dimples on the surface of Al granules was given. Practical significance. Taking into account the new obtained results, a technique for constructing distributions of volumes of halo and cores of plasma channels and determining their parameters has been developed.

Розширення можливостей та підвищення якості продукції іскроерозійних технологій потребує залучення не тільки електричних, а і оптичних методів контролю процесів. Проблема. Створення методів керування властивостями іскроерозійних частинок на основі даних оптичних вимірювань потребує вирішення декількох науково-практичних задач. Мета. Визначення законів розподілу об’ємів кольорових гало та білих іскрових ядер плазмових каналів, які виникають у шарі гранул металів в результаті протікання імпульсних розрядних струмів. Методологія. Аналіз якості апроксимації отриманих в ході експериментів розподілів об’ємів складових плазмових каналів низкою теоретичних розподілів. Отримані результати. Найбільш адекватним серед усіх розглянутих теоретичних законів, що описують розподіли об’ємів гало і ядер плазмових каналів, а також їхніх відношень, є логарифмічно-нормальний. Оригінальність. Вперше досліджено розподіли об’ємів гало і ядер плазмових каналів та наведено їх порівняльний аналіз з розподілами розмірів ерозійних частинок і лунок на поверхні гранул Al. Практична значимість. Розроблено методику побудови розподілів об’ємів гало і ядер плазмових каналів.
Keywords: plasma channels; spark; discharge current; statistical distributions; metal granules; erosion particles; плазмові канали; іскра; розрядний струм; статистичні розподіли; металеві гранули; ерозійні частинки